Pemberdayaan Masjid oleh Mahasiswa KpM STAIN Meulaboh di Gampong Alue Meutuah Kecamatan Meukek Kabupaten Aceh Selatan - Efendi, Sumardi; Kasih, Dar; Bahgia, Riyan; Amfal, Sampri; Kifli, Ristiwa Firzanita; Fazli, Fazli; Safrida, Safrida; Sumayyah, Farah; Mauliyanti, Mauliyanti; Hasliani, Cici (Yayasan Abdurrauf Cendekia Nusantara, 2024)
Empowerment of Mosques by Student Community Research Groups (KPM) of STAIN Meulaboh in Alue Meutuah Village, Meukek District, South Aceh Regency, is an initiative aimed at enhancing the role of mosques in the social development of the local community. The background of this research lies in the necessity to augment the role of mosques as centers of social and religious activities capable of empowering the community, particularly in rural areas. The objective of this research is to enhance the role of mosques in social and religious activities and to strengthen student involvement in community service. The methodology employed is Participatory Action Research (PAR), involving students in the identification of issues, planning, implementation, and evaluation of mosque empowerment programs. The outcomes of this endeavor encompass heightened awareness among the community regarding the role of mosques as centers of social and religious activities, increased community involvement in mosque activities, and the development of local potential through social, economic, and educational activities conducted within the mosque premises. Additionally, through active student engagement, a harmonious relationship between higher education institutions and the community is fostered, leading to the formation of sustainable cooperation networks for better local development. Abstrak: Pemberdayaan Masjid oleh Mahasiswa Kelompok Penelitian Masyarakat (KPM) STAIN Meulaboh di Gampong Alue Meutuah, Kecamatan Meukek, Kabupaten Aceh Selatan, merupakan inisiatif yang bertujuan untuk meningkatkan peran serta masjid dalam pembangunan sosial masyarakat setempat. Latar belakang dari penelitian ini adalah kebutuhan akan peningkatan peran masjid sebagai pusat kegiatan sosial dan keagamaan yang dapat memberdayakan masyarakat, terutama di peGampongan. Tujuan dari penelitian ini adalah untuk meningkatkan peran masjid dalam kegiatan sosial dan keagamaan serta memperkuat keterlibatan mahasiswa dalam pengabdian masyarakat. Metode pengabdian dilakukan melalui Pendekatan Partisipatif Aksi Riset (PAR) yang melibatkan mahasiswa dalam identifikasi permasalahan, perencanaan, pelaksanaan, dan evaluasi program pemberdayaan masjid. Hasil dari pengabdian ini mencakup peningkatan kesadaran masyarakat tentang peran masjid sebagai pusat kegiatan sosial dan keagamaan, peningkatan keterlibatan masyarakat dalam kegiatan masjid, serta pengembangan potensi lokal melalui kegiatan sosial, ekonomi, dan pendidikan yang dilakukan di masjid. Selain itu, melalui keterlibatan aktif mahasiswa, tercipta hubungan yang harmonis antara perguruan tinggi dan masyarakat, serta terbentuknya jaringan kerjasama yang berkelanjutan untuk pembangunan lokal yang lebih baik.